Government Pay Policies and Structural Adjustment. (IMF Working Papers; Working Paper, 1988)
The paper provides an overview of the main elements of pay systems that are typically used to remunerate government employees and, with reference to the experience of developed and developing countries, discusses structural issues frequently arising in the formulation of government pay policies: (1) the role of fringe benefits in the compensation system; (2) the pros and cons of a greater merit orientation in the pay system and of special pay schemes designed to remunerate staff at the professional and managerial level; and (3) factors determining internal pay differentials with special emphasis on the compressing effect of flat amount cost of living adjustments.